The family plot : a novel - Collins, Megan, 1984- (Atria Books, 2021)
"At twenty-six, Dahlia Lighthouse has a lot to learn when it comes to the real world. Raised in a secluded island mansion deep in the woods and kept isolated by her true crime-obsessed parents, she spent the last several years living on her own, but unable to move beyond her past-especially the disappearance of her twin brother Andy when they were sixteen. With her father's death, Dahlia returns to the house she has avoided for years. But the rest of the Lighthouse family arrives for the memorial, a gruesome discovery is made: buried in the reserved plot is another body-Andy's, his skill split open with an ax. Each member of the family handles the revelation in unusual ways. Her brother Charlie pours his energy into creating a family memorial museum, highlighting their research into the lives of famous murder victims; her sister Tate forges ahead with her popular dioramas portraying crime scenes; and their mother affects a cheerfully domestic facade, becoming unrecognizable as the woman who performed murder reenactments for her children. As Dahlia grapples with her own grief and horror, she realizes that her eccentric family, and the mansion itself, may hold the answers to what happened to her twin"--